2023
DOI: 10.1002/admt.202201686
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Transformation Inspired Multifunctional Cylindrical Vessels with Programmable Stoma‐Shaped Biomimetic Openings

Abstract: Pattern transformation in a periodic porous structure has inspired multifarious mechanical metamaterials/metastructures due to the induced unusual negative Poisson's ratio behavior of macroscopic materials. Recently, it has been leveraged to architect a variety of designable and multifunctional structural members. Inspired by this design methodology, a novel porous cylindrical shell, which is perforated by a large number of staggered openings, is constructed and investigated meticulously. A stable, anti‐distur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…[28] In the same vein, Sun et al designed a novel 3D porous cylindrical shell with stable, anti-disturbed, and controllable waisted deformation to manipulate multiple functions, including reagent release, underwater sampling, and flow control. [29] In addition, Ran et al developed permeable stoma-like carbon nanotubes anchored with Sn 4 P 3 , which were applied as an anode in sodium-ion batteries. [30] To date, studies have been reported on the biomimetic structures of guard cells, especially actuating mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[28] In the same vein, Sun et al designed a novel 3D porous cylindrical shell with stable, anti-disturbed, and controllable waisted deformation to manipulate multiple functions, including reagent release, underwater sampling, and flow control. [29] In addition, Ran et al developed permeable stoma-like carbon nanotubes anchored with Sn 4 P 3 , which were applied as an anode in sodium-ion batteries. [30] To date, studies have been reported on the biomimetic structures of guard cells, especially actuating mechanism.…”
Section: Introductionmentioning
confidence: 99%